(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Acute appendicitis is the most encountered surgical dilemmas, this attributed to the lack of unique symptoms or signs and the low sensitivity of available laboratory tests.Aim of study: to assess the ability of complete blood count parameters in diagnosing acute appendicitis.Patients & methods: a case control study done at a general surgical hospital over 1 year during which all patients with clinical features of acute appendicitis and were candidates for appendectomy were enrolled. Diagnosis was confirmed by histopathological study and classified into inflamed appendix [group A], and normal appendix group [group B]. Control group [group C] included 50 healthy adults.Results: A total of 115 patients were enrolled, group A (91 cases), group B (24 cases), and group C (50 cases). Mean platelet volume (MPV), neutrophil-to-lymphocyte ratio (NLR) and Platelet-Lymphocyte ratio (PLR) were significantly different from control and from cases of negative appendectomies with sensitivity (SN) and specificity (SP) as follow: MPV SN 90.1%, SP 79.7%, NLR SN 89%, SP 70.3%, PLR SN 83.5%, SP 74.3%Conclusion: The use of the complete blood count parameters MPV, NLR and PLR sensitive and specific for diagnosis of acute appendicitis and can be used as an aid in difficult diagnoses to reduce the rate of negative appendectomies.